Regional differences in AIDS and non-AIDS related mortality in HIV-positive individuals across Europe and Argentina: the EuroSIDA study. - Joanne Reekie (PLoS ONE, 2012)
BACKGROUND: Differences in access to care and treatment have been reported in Eastern Europe, a region with one of the fastest growing HIV epidemics, compared to the rest of Europe. This analysis aimed to establish whether there are regional differences in the mortality rate of HIV-positive individuals across Europe, and Argentina. METHODS: 13,310 individuals under follow-up were included in the analysis. Poisson regression investigated factors associated with the risk of death. FINDINGS: During 82,212 person years of follow-up (PYFU) 1,147 individuals died (mortality rate 14.0 per 1,000 PYFU (95% confidence interval [CI] 13.1-14.8). Significant differences between regions were seen in the rate of all-cause, AIDS and non-AIDS related mortality (global p<0.0001 for all three endpoints). Compared to South Europe, after adjusting for baseline demographics, laboratory measurements and treatment, a higher rate of AIDS related mortality was observed in East Europe (IRR 2.90, 95%CI 1.97-4.28, p<.0001), and a higher rate of non-AIDS related mortality in North Europe (IRR 1.51, 95%CI 1.24-1.82, p<.0001). The differences observed in North Europe decreased over calendar-time, in 2009-2011, the higher rate of non-AIDS related mortality was no longer significantly different to South Europe (IRR 1.07, 95%CI 0.66-1.75, p = 0.77). However, in 2009-2011, there remained a higher rate of AIDS-related mortality (IRR 2.41, 95%CI 1.11-5.25, p = 0.02) in East Europe compared to South Europe in adjusted analysis. INTERPRETATIONS: There are significant differences in the rate of all-cause mortality among HIV-positive individuals across different regions of Europe and Argentina. Individuals in Eastern Europe had an increased risk of mortality from AIDS related causes and individuals in North Europe had the highest rate of non-AIDS related mortality. These findings are important for understanding and reviewing HIV treatment strategies and policies across the European region.